1956
DOI: 10.1021/jo01116a006
|View full text |Cite
|
Sign up to set email alerts
|

Nitrile Groups. IV. The Catalyzed Reaction of Nitriles with Amines in Water1

Abstract: The reaction of unsubstituted aliphatic nitriles, such as acetonitrile and benzonitrile, with amines in water is catalyzed by such different compounds as hydrochloric acid, acetic acid, and thiophenol and is particularly well catalyzed by hydrogen sulfide and thioacetamide. The hydrogen sulfide catalysis leads to either substituted amides (with primary amines at 100-150°, with morpholine at 100-150°, and with piperidine and diethylamine at 150°) or unsubstituted amides (with piperidine and diethylamine at 100°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1970
1970
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Melting points were determined on a MEL-TEMP capillary melting point apparatus equipped with a Flucke 51 digital thermometer. 1 H NMR (300 MHz) and 13 C NMR (75 MHz) spectra were recorded on a Gemini 300 NMR spectrometer in CDCl 3 (with TMS for 1 H and chloroform-d for 13 C as the internal reference). Elemental analyses were performed on a Carlo Erba-1106 instrument.…”
Section: Methodsmentioning
confidence: 99%
“…Melting points were determined on a MEL-TEMP capillary melting point apparatus equipped with a Flucke 51 digital thermometer. 1 H NMR (300 MHz) and 13 C NMR (75 MHz) spectra were recorded on a Gemini 300 NMR spectrometer in CDCl 3 (with TMS for 1 H and chloroform-d for 13 C as the internal reference). Elemental analyses were performed on a Carlo Erba-1106 instrument.…”
Section: Methodsmentioning
confidence: 99%
“…5, 6 Despite the potential of this transformation, the synthesis of N ‐alkyl amides from nitrile and amine reagents has obtained very little attention so far. Except for some specific dinitriles and acetonitrile,7, 8a the combined hydrolysis–aminolysis reaction of a nitrile group with primary or secondary amines requires a catalyst to give a substituted amide and ammonia as a high yield product at mild temperature 8. 9 The most promising results have been observed with ruthenium and platinum catalysts 8.…”
Section: Introductionmentioning
confidence: 99%
“…However, this required a 24‐hour reaction time at 160 °C with no less than 3 mol % of [RuH 2 (PPh 3 ) 4 ] and a solvent 8b. De Benneville and co‐workers demonstrated that an eight‐hour reaction time at 150 °C is sufficient to obtain the desired product in 83 % yield by using H 2 S as a catalyst 8a. Although the reaction did not require a solvent, 25 mol % of the highly undesirable H 2 S is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Many chemical transformations of the nitrile group in polyacrylonitrile (PAN) to obtain polymers with new properties are k n~w n , l -~ but the reaction of PAN with aliphatic amines which contain labile hydrogen atoms is less inve~tigated.~ It is known that the low-molecular-weight nitrile compounds react with difficulty with such amines, the reaction products being highly dependent on amine basicity and steric configuration. 6 The reaction of di-nitrile compounds with amines in the presence of water takes place without a catalyst in the case of a-, N ,N -dimethyl-1,3-diaminopropane (A), N,N-dibutyl-1,3-diaminopropane (B), and Nfl-dimethyl-1,2-diaminoethane (C) were previously vacuum distilled. N,N-bis(2-hydroxyethyl)-1,3-diaminopropane (D) was of analytical grade.…”
Section: Introductionmentioning
confidence: 99%